Reconstructing the Concept of Islamic Politics in Early Muslim Intellectual History: A Historical–Intellectual Analysis - M. Desta Ramadoni (Medan Resource Center, 2026)
This study examines the dynamics and contemporary relevance of Islamic political thought within the early Muslim intellectual tradition, spanning from the prophetic period of Muhammad to the Abbasid era. This formative phase established foundational principles such as shura (consultation), amanah (trust), the rule of law, and social pluralism, which functioned not only as normative-theological constructs but also as practical frameworks for governance. The research addresses how these principles were historically constructed and how their meanings have shifted in modern interpretations. Employing a qualitative design, the study utilizes historical methods and a historical-intellectual approach through extensive library research. Data were collected from classical and contemporary sources and analyzed through heuristic procedures, source criticism, interpretation, and historiography in a descriptive-analytical manner. The findings reveal that early Islamic political thought developed as an integrative ethical-intellectual system that harmonized normative values with socio-political realities. In contrast, contemporary discourse often reduces Islamic politics to formal power structures, religious symbolism, and identity politics due to decontextualized readings and reductive analytical frameworks. This study argues for a return to a historically grounded intellectual framework to restore the conceptual richness of Islamic political thought and to enable its meaningful reinterpretation in modern contexts.